SPACE SECURITY SYSTEM USING INFRA RED TECHNOLOGY - Ichwal Kurniawan; Indrianto Indrianto. Skom. MT (Jurnal Sistem Komputer, 2010)
By leveraging existing technology and at this point, these tools can we design a smaller and simpler, without reducing the reliability of these tools. In the design of this tool there are some weaknesses, namely in the operation of the tool is basically due to the quality factor of the quality of each component is different from the standardization of a component.